PostKasai Portoenterostomy Dissection of a Branch of the Right Hepatic Artery – A Rare Complication - Charu Sharma; Nitinkumar Borkar; Revanth Kalla; C. Ashwin; Nihar Kathrani (Journal of Indian Association of Pediatric Surgeons)
Hepatic artery branch dissection is a lesser-known complication after biliary atresia surgery. The presentation is massive upper gastrointestinal bleeding and rapid drop in hemoglobin levels. We present a 6-week-old infant with biliary atresia who had dissection of a branch of the right hepatic artery which was managed by angioembolization.